Optimization for real time strategy games - Ng, Heng Khai. (2013)
This project seeks to optimize the build order for the first minutes into a Real-Time Strategy (RTS) game. The myriad of possible paths a player could take achieve this goal is derived. From these, the optimal path that the player can follow is found and listed with its relevant required timings step by step with certain reasonable constraints. This is to help to keep the optimization manageable, such that it can be done in a realistic timeframe, using reasonable computational requirements, so that these computations can be done on the average computer used by the potential user. The generated build list gives the player has a solid foundation at the start of the game, in which he or she can then focus their energies into managing and developing, and adapting their more strategies for the later part of the game.